Happy Birthday, America - Osborne, Mary Pope; Catalanotto, Peter (Brookfield, Conn. : Roaring Brook Press, 2003)
The whole family joins in a lively small-town celebration of Independence Day, including a parade, a picnic, music, and fireworks. An author's note explains the origin of the celebration of July 4th.
Accelerated Reader AR